Global Food Security and Wellness - Barbosa-Cánovas, Gustavo V.; María Pastore, Gláucia; Candoğan, Kezban; Medina Meza, Ilce G.; Caetano da Silva Lannes, Suzana; Buckle, Ken.; Yada, Rickey Y.; Rosenthal, Amauri; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2017)
This book is based on selected papers from keynote and symposium sessions given at the 16th International Union of Food Science and Technology (IUFoST) World Congress, held in Foz do Iguaçu, Brazil, in August, 2012. The theme of the Congress was the challenges faced by food science in both the developed and developing regions of the world. The symposia featured prominent, world-renowned keynote and plenary speakers and young researchers, and the technical sessions covered the whole spectrum of basic and applied food science and technology, including consumer issues and education, diets and health, ethnic foods and R&D.
Supporting Country-driven Innovations and Agrifood Value Chains for Poverty and Hunger Reduction -- Preserving Food after Harvest is an Integral Component of Food Security -- Microbiological Safety of Fruit and Vegetables in the Field, During Harvest and Packaging: A Global Issue -- Ensuring Food Safety in Developing and Developed Countries: Aspects Associated with the Use of Veterinary Drugs in Fish Farming in Brazil -- Functional Dairy Products -- Brazilian Native Fruits as a Source of Phenolic Compounds -- Technology and Nutrition Opportunities for Healthful Foods from Morama Beans, an Emerging Crop in Botswana -- Advancements in Obtaining and Utilizing Bovine Milk Proteins in Foods and Nutrition -- Chocolate and Cocoa Products as a Source of Health and Wellness -- Advances on the production and Application of Peptides for Promoting Human Health and Food Security -- Memorial -- IUFoST Distance-Assisted Training Program -- Food Science and Technology Undergraduate and Graduate and Graduate Curricula in North America -- Food Science and Technology Curricula in Africa: Meeting Africa's New Challenges -- Yeasts from Traditional Cheeses for Potential Applications -- Beta-lactoglobulin Fibril Dispersions: Structural and Rheological Characteristics -- Animal Welfare and Meat Quality: Methodologies to Reduce Pre-slaughter Stress in Boiler Chicken -- Protein Oxidation in Meat and Meat Products: Challenges for Antioxidative Protection -- Religious Slaughter of Animals: International Efforts to Meet This Need Responsibly -- Mitigation of Acrylamide Formation in Highly Consumed Foods -- Scale-up Issues and Cost of Manufacturing Bioactive Compounds by Supercritical Fluid Extraction and Ultrasound Assisted Extraction -- Multiphysics Modelling of Innovative Food processing Technologies -- Ultrasound Assisted Freezing of Fruits and Vegetables: Design, Development and Applications -- Characterization of Microbial Inactivation by Microwave Heating. .
Keywords: Food science; Nutrition .; Public health; Food Science; Nutrition; Public Health